Benefits of dry comminution of biomass pellets in a knife mill - Williams, Orla; Lester, Edward; Kingman, Sam; Giddings, Donald; Lormor, Stephen; Eastwick, Carol (Elsevier, 2017)
The potential benefits of dry comminution in a knife mill for a diverse range of biomass 6 pellets are explored. The impact of dry comminution on energy consumption, particle size and shape, 7 is examined as well as the link between milling and mechanical durability. Biomass pellet comminution 8 energy was significantly lower (19.3-32.5 kW h t-1 [fresh] and 17.8-23.2 kW h t-1 [dry]) than values 9 reported in literature for non-densified biomass in similar knife mills. The impact of drying was found 10 to vary by feedstock. Dry grinding reduced milling energy by 38% for mixed wood pellets, but only 2% 11 for steam exploded pellets. Particle size and shape, particle distribution dispersion, and distribution 12 shape parameters changes between fresh and dry milling were also material dependent. Von Rittinger 13 analysis showed that to maximise mill throughput, pellets should be composed of particles which can 14 pass through the screen and thus have a neutral size change. A strong correlation was found between 15 pellet durability and energy consumption for fresh biomass pellets. Dry grinding has the potential to 16 significantly reduce energy consumption without compromising the product particle size, as well as 17 enhancing product quality and optimising biomass pellet comminution and combustion.